2015
DOI: 10.1057/jors.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Is simulation in health different?

Abstract: It is often stated that health simulation is quite different and even that it is more difficult than in other sectors. But, is simulation in health really different to simulation in other sectorselsewhere? In this paper we explore this question through a survey of simulation modellers and academics. We elicit their opinions across a range of factors concerning the difficulties of health modelling against modelling in other domains. The analysis considers the responses of the whole group of respondents and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Cultural, practical and political aspects have been identified to explain this situation (Jahangirian et al 2015;Tako and Robinson 2014). Overall, modellers agree that "simulation in healthcare is different" (Tako and Robinson 2014). The same discussions have occurred regarding lean management (Young and McClean 2008;Radnor, Holweg, and Waring 2012).…”
Section: Transferring Industrial Approaches To Healthcare Organisationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Cultural, practical and political aspects have been identified to explain this situation (Jahangirian et al 2015;Tako and Robinson 2014). Overall, modellers agree that "simulation in healthcare is different" (Tako and Robinson 2014). The same discussions have occurred regarding lean management (Young and McClean 2008;Radnor, Holweg, and Waring 2012).…”
Section: Transferring Industrial Approaches To Healthcare Organisationsmentioning
confidence: 91%
“…Jahanagirian et al (2012) found that only 8% of simulation papers in healthcare involved "a significant level of user/stakeholder engagement in the simulation part", as opposed to "hypothetical Problem-Solving papers" or "methodological papers", whereas "real problem solving papers" accounted for 49% of the simulation papers in commerce and 39% in defense. Cultural, practical and political aspects have been identified to explain this situation (Jahangirian et al 2015;Tako and Robinson 2014). Overall, modellers agree that "simulation in healthcare is different" (Tako and Robinson 2014).…”
Section: Transferring Industrial Approaches To Healthcare Organisationsmentioning
confidence: 99%
“…This includes the amount and type of information that the software can process, and the judgements involved in deciding what information to include. This is aggravated by the complex structure of hospital operations [28]. For instance, dividing patients into different types comes as a result of the difficulty in taking into consideration all patient illnesses both in terms of software capability and the ability to form a valid or accurate model.…”
Section: Model Limitationsmentioning
confidence: 99%
“…In a survey among simulation practitioners Tako and Robinson (2015) discovered also a number of other differences between simulation in health care and other sectors. Among these differences were more complex systems with less evident structure and messier problems, difficulties in collecting and accessing data, difficulties in developing generic models and ensuring implementation.…”
Section: Simulation In Health Carementioning
confidence: 99%